2022
DOI: 10.1002/anie.202114936
|View full text |Cite
|
Sign up to set email alerts
|

The Assembly and Jamming of Nanoparticle Surfactants at Liquid–Liquid Interfaces

Abstract: Using the interactions between nanoparticles (NPs) and polymeric ligands to generate nanoparticle surfactants (NPSs) at the liquid–liquid interface, the binding energy of the NP to the interface can be significantly increased, irreversibly binding the NPSs to the interface. By designing a simplified NPS model, where the NP size can be precisely controlled and the characteristic fluorescence of the NPs be used as a direct probe of their spatial distribution, we provide new insights into the attachment mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The S/W interface can support the assembly of particles that diffuse and stabilize the interface, opening the possibility for the design of functional soft materials, [ 53 ] for instance, by Pickering emulsion stabilization. [ 54 ] We observed that with the evaporation of the solvent, betulin crystallized in situ (Figure 5F), and the crystals stabilized the S/W interface. The solvent/water (L/L) interfacial tension γ of betulin (0.8% concentration) was determined with the pendant drop technique.…”
Section: Resultsmentioning
confidence: 99%
“…The S/W interface can support the assembly of particles that diffuse and stabilize the interface, opening the possibility for the design of functional soft materials, [ 53 ] for instance, by Pickering emulsion stabilization. [ 54 ] We observed that with the evaporation of the solvent, betulin crystallized in situ (Figure 5F), and the crystals stabilized the S/W interface. The solvent/water (L/L) interfacial tension γ of betulin (0.8% concentration) was determined with the pendant drop technique.…”
Section: Resultsmentioning
confidence: 99%
“…Introducing host–guest chemistry of macrocycles into liquid‐liquid interfaces provides an alternative strategy to prepare structured liquids with multiple stimuli‐responsiveness, [21–23] due to the self‐selectivity and environmental responsiveness of host–guest interactions. Very recently, by using the host–guest interactions between α‐cyclodextrin modified NPs and azobenzene‐terminated polymeric ligands, [24] or β‐cyclodextrin modified NPs and ferrocene‐terminated polymeric ligands, [25] NPSs and structured liquids with photo or redox responsiveness have been constructed.…”
Section: Figurementioning
confidence: 99%
“…[ 10 ] Moreover, by functionalizing the surface of the NPs and the ligands with different types of complementary groups, for example, cation‐anion pairs or cyclodextrin‐based host−guest recognition motifs, multiple stimuli responsiveness including pH, photo, and redox can be integrated into the NPSs and, the resultant interfacial assemblies. [ 11–14 ] However, despite these achievements based on NPSs, the exploration of other noncovalent interactions at the oil‐water interface is still limited. It is also challenging to stabilize or structure the interface as the NP size decreases to the molecular level, i.e., small molecules, due to the very low binding energy, unless the small molecules interact with each other, forming an aggregate, either in solution or at the interface, and transforming the size scale of the unit adsorbed to the interface.…”
Section: Introductionmentioning
confidence: 99%